PSYCHOLOGICAL VULNERABILITIES OF REMOTE WORKING INTERACTION - Bessonova , Yu. V. (Modern Psychology, 2022)
Remote work interaction is becoming the most important trend in employment management. The work-from-home online job affected not only in technical occupations who have experience in remote working. Different professions were simultaneously involved in online interaction, regardless of skills, willingness or nature of its work. Unlike human- computer interaction, main feature of this interaction is communication between people that built outside the logic of the programming language and it is due to socio-psychological mechanisms rather than technical re- quirements. Online interaction depends on communication processes, cyber shadow saving / data updatability, anonymity and self-disclosure degree, etc. The comparative features of online and offline communication, the spe- cifics of network language and communication can be considered relatively studied at the present time. However, online professional communication is beyond the focus of the researchers’ attention, including the exposure of such online communication to the influence of motivation, psychological barriers, user beliefs, preferences and attitudes. User experience, affective support, and user attribution and motivation were identified as the priority predictors of remote working efficiency in the conditions of a massive and sudden shift to new working conditions.